Syeikh Abdul Qadir Bin Abdur Rahim Al-Fathani Bukit Bayas (1864) Towards Hadith Works and Writings of Fiqh Muamalat al-Maliyyah: An Introduction of The Malay Jawi Manuscript Entitled: Risalah fi Bayani Hukmi Bai’i war Riba - Z N, Mohd Khairul Nizam; Mahmud Ahmad; Nurul Jannah (Postgraduate Program at Sunan Gunung Djati State Islamic University, Postgraduate Program at Academy for Islamic Studies University of Malaya, 2024)
Vol : 2, No :1